2012
DOI: 10.1016/j.sdentj.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Female sex hormones and periodontal health-awareness among gynecologists – A questionnaire survey

Abstract: Women have special periodontal health care considerations, and there is a need for better oral health education among caregivers. Our results suggest that increasing dental health awareness among gynecologists would significantly improve women's health and pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 22 publications
6
21
4
1
Order By: Relevance
“…Ninety percent of the participants in the present study were aware of the effects of changes in female sex hormones on gingival status. This is different from the results of studies by Cohen 28 and Patil et al, 11 which indicated the awareness of 74.7% and 32.98% of participants, respectively, about the effects of women's hormonal changes on gingival health. This study also showed no statistically significant relationships between the age or the occupational experience of the participants and their level of knowledge, consistent with the results reported by Shah et al, 29 who emphasized the absence of a statistically significant relationship between age and awareness of participants.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Ninety percent of the participants in the present study were aware of the effects of changes in female sex hormones on gingival status. This is different from the results of studies by Cohen 28 and Patil et al, 11 which indicated the awareness of 74.7% and 32.98% of participants, respectively, about the effects of women's hormonal changes on gingival health. This study also showed no statistically significant relationships between the age or the occupational experience of the participants and their level of knowledge, consistent with the results reported by Shah et al, 29 who emphasized the absence of a statistically significant relationship between age and awareness of participants.…”
Section: Discussioncontrasting
confidence: 94%
“…On the other side, these results are different from the results reported by Cohen et al, 28 who reported that the awareness of gynecologists about periodontal diseases increased proportional to their work experience. 82.5% of the participants of the present study considered premature delivery and 75% of them considered low birth weight as the consequences of maternal periodontal disease, which is consistent with the results of studies by Patil et al, Shah et al, Suri, Cohen, Hashim and Laslowski, in which most of the participants considered periodontal disease as a risk factor for adverse outcomes of pregnancy, including low birth weight or premature delivery, 11,[28][29][30][31][32][33] while in the study by Shenay, 26 fewer participants considered periodontal disease as a risk factor for inappropriate pregnancy complications despite their proper knowledge about oral manifestations of periodontal diseases. In a study by Bahalla, 34 the participants only considered vaginal infection as a cause of low birth weight or premature delivery and only reported infectious endocarditis as the main consequence of periodontal disease.…”
Section: Discussionsupporting
confidence: 90%
“…11 Unfortunately, pregnant women and their ANC providers are unaware of the implications of poor oral health and seldom seek dental care during pregnancy. 9,10,20 There is increasing evidence to support this lack of awareness among medical doctors about periodontal health consequences and long-term risk associated with poor oral hygiene especially during pregnancy. 7,9,21,22 Similarly, there is limited evidence about the perceptions of such ANC providers in Nepal towards provision of prenatal oral health care.…”
Section: Discussionmentioning
confidence: 99%
“…Most survey items were derived and modified from existing studies exploring the knowledge of medical doctors regarding oral health and awareness about possible implications during pregnancy. 7,[9][10][11] The proforma was reviewed by experts to establish content validity and then tested twice in a group of medical doctors practicing in the Kathmandu city (initially in 25 doctors, then 34). Survey content, clarity and length were modified and improved in response to the reviews.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] In the present study, about 37.5%, 36%, and 17% of the study participants said that hormonal changes, poor oral hygiene, and plaque, respectively, cause inflamed gums among pregnant women. In contrast, 98.3% of Indian gynecologists agreed that hormonal changes during pregnancy could cause inflamed gums[ 19 ] and 89.5% of the medical doctors in Tanzania believed poor oral hygiene was the main cause of periodontal disease. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%